Colour stability of CAD-CAM laminate veneer after aging and exposure to food spices - Enas Abdalla Etajuri; Noorhayati Raja Mohd; Zubaidah Zanul Abidin; Khor, Xin Ee; Lim, Joelle Sin Yi; Siti Fauzza Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2025)
The colour stability of CAD-CAM ceramic veneer restoration is a crucial factor for the long-term success of the restoration. However, the effect of food spices on CAD-CAM ceramic has not been evaluated. The purpose of this study was to evaluate the colour stability of CAD-CAM laminate veneer materials after artificial aging and exposure to turmeric and paprika staining solutions. CAD-CAM ceramic slices (N=72; shade; A2; diameter 9 mm × 7 mm) were prepared using feldspathic ceramic (n=36) and zirconia-reinforced lithium disilicate (n=36). Each type of ceramic material is divided into two thicknesses, 0.5 mm (n=18) and 0.7 mm (n=18). The ceramic slices were cemented onto central incisors. The samples were subjected to accelerated aging for 1000 cycles. Samples were further divided into 3 subgroups (n=6): distilled water (control), turmeric, and paprika staining solutions, and soaked for 24 h. Spectrophotometric colour measurement was recorded, and colour difference (ΔE) was calculated after aging (ΔE1), and after 24 h of immersion in spices solutions (ΔE2). Two-way analysis of variance and Bonferroni’s test were used for the statistical analysis (α=.05). ΔE1 means were not significantly influenced by ceramic materials (P=0.770) and thicknesses (P= 0.162). ΔE2 means were significantly affected by the interaction between thickness and staining solutions in both materials (P <0.05). Both ceramic veneers presented the highest colour change after immersion in turmeric solution. Ceramic veneers show colour changes after artificial aging. Turmeric shows a significant effect on the colour of ceramic veneer after staining. Ceramic thickness influences the amount of colour change after aging and staining.